THE EFFECTIVENESS OF ANDROID-BASED FIRE EXTINGUISHER INSPECTIONS USING QUICK RESPONSE CODES (QR CODES) AT PT INDUSTRI JAMU DAN FARMASI SIDO MUNCUL TBK. - Luthfiyatul Karimah; Imam Purnomo; Ristiawati Ristiawati (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
In industrial settings, one of the key measures for ensuring safety is protecting against fire hazards. Therefore, a series of efficient preventive and response measures is necessary to reduce the risk of fire. In Indonesia, one approach to addressing the threat of fire involves the use of portable fire extinguishers (APAR). This study aims to develop a Portable Fire Extinguisher (APAR) inspection system using Android-based QR code technology. The study employs an R&D approach based on the Four-D (4D) model, which consists of four stages: define, design, develop, and disseminate. Data were obtained through a feasibility test (expert users) conducted by subject matter experts as well as media and systems experts, and through pre- and post-testing. The results of the subject matter experts’ review yielded a score of 82.5%, categorized as “highly feasible.” The media and systems experts conducted validation and achieved a score of 85%, also categorized as “highly feasible.” The trial results showed an increase in scores from 89 using the manual method to 96 with the QR code system. Therefore, the developed system is considered effective and more efficient in supporting the fire extinguisher inspection process and the management of workplace safety data.